Pseudomonas aeruginosa Bloodstream Infection, Resistance, and Mortality: Do Solid Organ Transplant Recipients Do Better or Worse? - Sabina Herrera; Laura Morata; Abiu Sempere; Miguel Verdejo; Ana Del Rio; Jose Antonio Martínez; Guillermo Cuervo; Marta Hernández-Meneses; Mariana Chumbita; Cristina Pitart; Pedro Puerta; Patricia Monzó; et al. (MDPI AG, 2023)
Background: The prevalence of antimicrobial resistance of Pseudomonas aeruginosa (P. aeruginosa) in solid organ transplant (SOT) recipients is higher than that of the general population. However, the literature supporting this statement is scarce. Identifying patients at risk of carbapenem resistance (CR) is of great importance, as CR strains more often receive inappropriate empiric antibiotic therapy, which is independently associated with mortality in bloodstream infections (BSIs). Methods: We prospectively recorded data from all consecutive BSIs from January 1991 to July 2019 using a routine purpose-designed surveillance database. The following variables were included: age, sex, type of transplant, use of vascular and urinary catheters, presence of neutropenia, period of diagnosis, treatment with steroids, origin of BSI, source of bacteremia, septic shock, ICU admission, mechanical ventilation, previous antibiotic treatment, treatment of bacteremia, and 30-day all-cause mortality. Results: We identified 2057 episodes of P. aeruginosa BSI. Of these, 265 (13%) episodes corresponded to SOT recipients (130 kidney transplants, 105 liver, 9 hearts, and 21 kidney-pancreas). Hematologic malignancy [OR 2.71 (95% CI 1.33-5.51), p = 0.006] and prior carbapenem therapy [OR 2.37 (95% CI 1.46-3.86), p < 0.001] were associated with a higher risk of having a CR P. aeruginosa BSI. Age [OR 1.03 (95% CI 1.02-1.04) p < 0.001], urinary catheter [OR 2.05 (95% CI 0.37-3.06), p < 0.001], shock at onset [OR 6.57 (95% CI 4.54-9.51) p < 0.001], high-risk source [OR 4.96 (95% CI 3.32-7.43) p < 0.001], and bacteremia caused by CR strains [OR 1.53 (95% CI 1.01-2.29) p = 0.036] were associated with increased mortality. Correct empirical therapy was protective [OR 0.52 (95% CI 0.35-0.75) p = 0.001]. Mortality at 30 days was higher in non-SOT patients (21% vs. 13%, p = 0.002). SOT was not associated with a higher risk of having a CR P. aeruginosa BSI or higher mortality. Conclusions: In our cohort of 2057 patients with P. aeruginosa BSIs, hematologic malignancies and previous carbapenem therapy were independently associated with a risk of presenting CR P. aeruginosa BSI. Age, urinary catheter, high-risk source, bacteremia caused by carbapenem-resistant strains, and severity of the infection were independently associated with mortality, whereas correct empirical therapy was a protective factor. An increasing trend in the resistance of P. aeruginosa was found, with >30% of the isolates being resistant to carbapenems in the last period. SOT was not associated with a higher risk of carbapenem-resistant BSIs or higher mortality.